Optimalisasi Budidaya Ikan Lele melalui Mitigasi Bahaya Penyakit Kuning di Dusun Embung Pas Lombok Barat - Rangga Idris Affandi; Zaenal Abidin; Peter Chen; Bagus Dwi Hari Setyono; Damai Diniariwisan; Thoy Batun Citra Rahmadani; Wastu Ayu Diamahesa; Nunik Cokrowati; Laily Fitriani Mulyani; Awan Dermawan (LPMP Imperium, 2026)
West Nusa Tenggara has strong aquaculture potential, particularly in freshwater catfish (Clarias sp.) farming. However, farmers in Embung Pas Hamlet, Sigerongan Village, face challenges due to limited knowledge of jaundice disease, which can lead to mass mortality and economic losses. This community service activity aimed to improve farmers’ knowledge and awareness regarding the identification, risks, prevention, and treatment of jaundice in catfish culture. The program was conducted on March 10, 2026, using a participatory approach through interactive lectures, discussions, demonstrations, and follow-up assistance. The materials included fish health management, disease symptoms, and control strategies. The results showed active participation and increased understanding among farmers, particularly in early detection and water quality management. Although minor constraints such as limited time and varying knowledge levels were encountered, the program was successfully implemented. Overall, this activity effectively enhanced farmers’ awareness and capacity in managing fish health sustainably.